2014
DOI: 10.1097/ccm.0000000000000332
|View full text |Cite
|
Sign up to set email alerts
|

Initial Lactate and Lactate Change in Post–Cardiac Arrest

Abstract: Introduction Rate of lactate change is associated with in-hospital mortality in post-cardiac arrest patients. This association has not been validated in a prospective multicenter study. Objective To determine the association between percent lactate change and outcomes in post-cardiac arrest patients. Methods Four-center prospective observational study conducted from June 2011 to March 2012. Inclusion criteria consisted of adult out-of-hospital non-traumatic cardiac arrest patients who were comatose after r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
107
3
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(135 citation statements)
references
References 33 publications
16
107
3
9
Order By: Relevance
“…Our results are in agreement with Donnino et al, a prospective study of lactate levels following cardiac arrest, which recorded a mortality rate of 80% in patients where initial lactate was greater than 10 mmol.l -1 [8].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Our results are in agreement with Donnino et al, a prospective study of lactate levels following cardiac arrest, which recorded a mortality rate of 80% in patients where initial lactate was greater than 10 mmol.l -1 [8].…”
Section: Discussionsupporting
confidence: 95%
“…The existing literature on acidosis in intensive care unit (ICU) mainly consists of analyses of specific causes of metabolic acidosis, with little on management of severe cases; there is no study comparing different causes [6][7][8][9]. As regards to shock with severe lactic acidosis with pH <7.2, observed mortality rate is about 50%, while several study have reported universal mortality in case of shock with lactic acidosis under pH 7.0 [10][11][12][13].…”
Section: Introductionmentioning
confidence: 95%
“…Thus, monitoring of lactate in this setting may be of more value to assess the severity of tissue hypoxia than just blood pressure or cardiac output. Other studies have also shown the prognostic value of admission blood lactate levels after CA and of changes in lactate levels in the hours after CA [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Roberts et al [8] did not record blood lactate levels and we observed that increased lactate concentrations after CA were significantly associated with ICU mortality. As high lactate concentrations are primarily a consequence of prolonged CA and/or severe subsequent hemodynamic impairment [22][23][24], lactate can be considered as an extracerebral variable that is predictive of poor outcome in these patients. Abnormalities in tissue perfusion occurring after CA may also potentially contribute to brain hypoperfusion and development of MOF [7].…”
Section: Discussionmentioning
confidence: 99%
“…Pieno rūgšties koncentracija kraujo serume atspindi anaerobinio metabolizmo proceso dydį. Tyrimais nustatyta, kad kuo didesnė pieno rūgšties koncentracija kraujo serume ir metabolinės acidozės gylis, tuo blogesnė baigtis ir didesnė mirštamumo rizika [28,29]. Miokardo pažeidimas, kuomet po išemijos einanti reperfuzija pažeidžia širdies ląsteles, buvo pastebėtas Jennings ir kol.…”
Section: Darbo Medžiaga Ir Metodaiunclassified